ANALISIS KEUNTUNGAN USAHA SIRUP SEGAR CV. SEGARINDO UTAMA - Novianty A. Gobel; Paulus A. Pangemanan; Welson M. Wangke; Joachim Dumais (Universitas Sam Ratulangi, 2015)
ABSTRACT Competitive ability of Indonesian products must be understood association with upstream and downstream sectors and need to be formulated sources of economic growth by making a comparison to other industrial countries . Pineleng two villages there Pineleng District of fresh syrup effort being developed by the Main CV.Segarindo . So far business has been running fresh syrup but not yet known in detail how big profits from the business because of the fresh syrup production process CV.Segarindo Main does not run continuously or in a period of only two times the production process . Issues that will be examined in this study is how much profit businesses CV.Segarindo Main fresh syrup . The purpose of this study was to determine the business benefits of fresh syrup CV.Segarindo Main . Expected results of the study in this research may provide information to businesses in managing the business of fresh syrup. The type of data that is in need exists in two forms , namely primary data and primary sekunder.Data data obtained from interviews with supervisors and owners of factories and secondary data is data that has been arranged in the form of written documents obtained from the Main CV.Segarindo . The data obtained in this study in descriptive analysis to determine the business benefits of fresh syrup Main CV.Segarindo using the formula advantage . The results of this study are business Main CV.Segarindo produce six types of products . Each product provides advantages , when run on an ongoing basis . The conclusion of this study is that the average profits of fresh syrup per 6 months in the Main CV.Segarindo overall gain of one year types of syrup that is Rp . 1,580.880.000,01 . The suggestion is to further increase business profits fresh syrup and implemented in continuous production process and search for new marketing areas in addition to the existing area .